ADAM28 promotes tumor growth and dissemination of acute myeloid leukemia through IGFBP-3 degradation and IGF-I-induced cell proliferation. (1st February 2019) - Zhang, Jia-Min; Wang, Chen-Cong; Zhang, Gao-Chao; Jiang, Qian; Yang, Shen-Miao; Fu, Hai-Xia; Wang, Qian-Ming; Zhu, Xiao-Lu; Zhu, Hong-Hu; Jiang, Hao; Wang, Yu; Lv, Meng; et al.
Abstract: ADAM28 has been shown to relate with tumor proliferation and prognosis. The expression of ADAM28 is up-regulated in acute myeloid leukemia (AML). However, the mechanism by which ADAM28 regulates the leukemic cell and the prognostic relevance with AML remain unknown. Here, we found that the expression level of ADAM28 was significantly elevated in AML patients suffering a relapse compared with those remaining in complete remission (CR). ADAM28 promoted the proliferation, migration and invasion in leukemic cells in vitro. Additionally, the increased expression of ADAM28 led to more IGFBP-3 degradation and IGF-I-induced cell proliferation. In a xenotransplantation mouse model, knockout of ADAM28 alleviated HL-60 cells growth and dissemination. The cumulative incidence of relapse (CIR) was significantly higher in patients with high ADAM28 expression. When separately considering the impact of ADAM28 on prognosis within the risk stratifications, patients with high ADAM28 expression levels had a significantly higher CIR in the favorable and intermediate-risk group but not in poor-risk group. Taken together, these data suggest a pivotal role for ADAM28 in regulating the proliferation and invasion of leukemic cells and in the prediction of relapse in AML patients. Highlights: ADAM28 enhanced the growth and dissemination of AML. ADAM28 led to IGFBP-3 degradation and IGF-I-induced leukemic cell proliferation. ADAM28 expression levels identified a high risk of relapse in patients with AML especially in favorable-risk group, and allotransplant might overcome the impact of ADAM28.